2018
DOI: 10.1371/journal.pcbi.1005970
|View full text |Cite
|
Sign up to set email alerts
|

The exclusive effects of chaperonin on the behavior of proteins with 52 knot

Abstract: The folding of proteins with a complex knot is still an unresolved question. Based on representative members of Ubiquitin C-terminal Hydrolases (UCHs) that contain the 52 knot in the native state, we explain how UCHs are able to unfold and refold in vitro reversibly within the structure-based model. In particular, we identify two, topologically different folding/unfolding pathways and corroborate our results with experiment, recreating the chevron plot. We show that confinement effect of chaperonin or weak cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 66 publications
4
43
0
Order By: Relevance
“…To overcome these problems, in vitro translation and mechanical unfolding experiments designed specifically to untie the polypeptide chain of YibK, YbeA and UCH-L1 showed that a decrease of the folding rate constant when threading the polypeptide chain is mandatory to reach the native state 23,24 . Besides the intramolecular non-native interactions evolved to overcome the free energy barrier of knotted proteins, it has been proposed that the cellular machinery, like chaperonins and the ribosome, can assist the folding of knotted proteins in vivo by promoting the formation of a knot in confined spaces 23,25,26 , by stabilizing key intermediates and establishing new folding routes 10,[26][27][28] , or by modulating the collapse by hydrophobic interactions 29 . These results support that knotted proteins must overcome a topological energy barrier derived from the threading of the polypeptide chain.…”
Section: Knots Are Remarkable Topological Features In Nature the Prementioning
confidence: 99%
“…To overcome these problems, in vitro translation and mechanical unfolding experiments designed specifically to untie the polypeptide chain of YibK, YbeA and UCH-L1 showed that a decrease of the folding rate constant when threading the polypeptide chain is mandatory to reach the native state 23,24 . Besides the intramolecular non-native interactions evolved to overcome the free energy barrier of knotted proteins, it has been proposed that the cellular machinery, like chaperonins and the ribosome, can assist the folding of knotted proteins in vivo by promoting the formation of a knot in confined spaces 23,25,26 , by stabilizing key intermediates and establishing new folding routes 10,[26][27][28] , or by modulating the collapse by hydrophobic interactions 29 . These results support that knotted proteins must overcome a topological energy barrier derived from the threading of the polypeptide chain.…”
Section: Knots Are Remarkable Topological Features In Nature the Prementioning
confidence: 99%
“…Other models concentrate on explaining the role of chaperones on the free energy landscape. According to recent results, the chaperone-induced speed up in kinetics stems probably from the reduced volume of folding, as the simulations show that the confinement [80,81,82] or ribosome-simulating basin [83,84] speeds up the folding of knotted proteins. Moreover, the chaperone confinement can alter the folding pathway.…”
Section: Advantages and Disadvantages Of A Complex Topologymentioning
confidence: 99%
“…To the best of our knowledge Virnau and co-workers were the first to explore the folding of protein DehI, embedding a deep 6 1 knot (18), and Soler et al (98) were the first to study the folding of a lattice model system with a shallow 5 2 knot (98). More recently, Sulkowska and coworkers, provided the first off-lattice results for protein Ubiquitin C-terminal Hydrolase L1 (UCH-L1) (PDB ID: 3irt) embedding a shallow 5 2 knot in its native structure (99).…”
Section: Knot Type and Knotting Mechanismmentioning
confidence: 99%